2018
DOI: 10.1186/s12879-018-3374-4
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of microbial pathogens and their antimicrobial pattern in operating theatres of peri-urban eastern Uganda: a cross-sectional study

Abstract: BackgroundMicrobial contamination of hospital environment, especially in operating theatres (OT) and other specialized units has greatly contributed to continuous and multiple exposure to nosocomial infections by patients and the public.We purposed to assess microbial contamination of operating theatres and antibacterial sensitivity pattern of bacteria isolated from theatres of Mbale Regional Referral Hospital, Eastern Uganda.MethodsWe employed a laboratory based cross-sectional study design. Swabbing of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 33 publications
2
22
1
Order By: Relevance
“…Elsewhere a study from Kawolo General Hospital in Uganda reported, S. aureus with the highest prevalence 46/61 (75.4%) [10]. On contrary our findings are different for some studies carry out in Cameroon (surveillance of nosocomial infections in YUTH) and Uganda (contamination of microbial pathogens in 4 operating theatre), where Klebsiella spp (27%), Pseudomonas spp (23.9) and Bacillus spp (17.5%) were found as common organisms respectively [6,11]. This difference can be due to the type and level of target hospital, units, type of specimen (hospital environment & hospitalized patients) and sample size.…”
Section: Results Of Culture According To the Profile And Prevalence Ofcontrasting
confidence: 76%
See 2 more Smart Citations
“…Elsewhere a study from Kawolo General Hospital in Uganda reported, S. aureus with the highest prevalence 46/61 (75.4%) [10]. On contrary our findings are different for some studies carry out in Cameroon (surveillance of nosocomial infections in YUTH) and Uganda (contamination of microbial pathogens in 4 operating theatre), where Klebsiella spp (27%), Pseudomonas spp (23.9) and Bacillus spp (17.5%) were found as common organisms respectively [6,11]. This difference can be due to the type and level of target hospital, units, type of specimen (hospital environment & hospitalized patients) and sample size.…”
Section: Results Of Culture According To the Profile And Prevalence Ofcontrasting
confidence: 76%
“…Besides, our study recovered 33 different species, whereas more the Uganda study 14 different organisms were reported in Mbale Regional Referral Hospital. On the different surfaces and settle plate establishment in 4 various operating theatres were swabbed and cultured [11]. This difference can be explained by obvious fact like distinction in study area, sample size, target articles brief methodology.…”
Section: Results Of Culture According To the Profile And Prevalence Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, coliforms showed high susceptibility to Imipenem followed by Staphylococcus aureus to Ciprofloxacin and this is comparable to a study done in Mbale Regional Referral Hospital, Eastern Uganda [37]. Furthermore, the study also showed that Staphylococcus aureus and other coliforms were resistant to Ciprofloxacin, Ceftriaxone, Gentamycin and Cotrimoxazole.…”
Section: Drug Susceptibility Pattern Of Bacterial Isolatessupporting
confidence: 88%
“…These findings are in agreement with findings in central Uganda in which Staphylococcus aureus and coliforms have been shown to be common pathogens in post-caesarean wound sepsis [19] . In addition, in Zanzibar, Staphylococcus aureus and E. coli were found to be common pathogens in sepsis [36], showing similarities in the common pathogens of Tanzania and Uganda, this may be attributed to the fact that Regional Referral Hospital, Eastern Uganda [37]. However findings are different from the study done in Muhimbili teaching Hospital [38], where the commonest organism isolated was Pseudomonas aeruginosa, this may be due to the difference in the standard of Hygiene (poor aseptic technique) as evidenced in this Hospital, since one nurse was responsible for cleaning and dressing 15 postoperative wounds hence putting patients at risk of cross infection.…”
Section: Common Bacterial Isolatesmentioning
confidence: 98%